2018
DOI: 10.1002/smll.201803015
|View full text |Cite
|
Sign up to set email alerts
|

Serpentine Ni3Ge2O5(OH)4 Nanosheets with Tailored Layers and Size for Efficient Oxygen Evolution Reactions

Abstract: Layered serpentine Ni3Ge2O5(OH)4 is compositionally active and structurally favorable for adsorption and diffusion of reactants in oxygen evolution reactions (OER). However, one of the major problems for these materials is limited active sites and low efficiency for OER. In this regard, a new catalyst consisting of layered serpentine Ni3Ge2O5(OH)4 nanosheets is introduced via a controlled one‐step synthetic process where the morphology, size, and layers are well tailored. The theoretical calculations indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 49 publications
5
39
0
2
Order By: Relevance
“…It is shown that there are two clear semicircles are presented in Nyquist plots. The semicircle in high frequency is corresponding to a charge transfer resistance ( R ct ) between the surface of the electrocatalyst and electrolyte . The semicircle in low‐frequency is associated with the adsorptive or formative resistance ( R oad ) of surface intermediates (e. g., O ad ) in the faradaic process, which reflects the mass transfer ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that there are two clear semicircles are presented in Nyquist plots. The semicircle in high frequency is corresponding to a charge transfer resistance ( R ct ) between the surface of the electrocatalyst and electrolyte . The semicircle in low‐frequency is associated with the adsorptive or formative resistance ( R oad ) of surface intermediates (e. g., O ad ) in the faradaic process, which reflects the mass transfer ability.…”
Section: Resultsmentioning
confidence: 99%
“…Both R ct and R oad are directly related to OER kinetics. In addition, there is solution resistance ( R s ), which relates to the resistance of electrolyte . For better comparison of these materials, a model of equivalent circuit (inset of Figure d) was built to fit the spectra of EIS.…”
Section: Resultsmentioning
confidence: 99%
“…Sumber Viskositas (21) Medis (10 ) Kelarutan Dalam Air (18) Bau (23 ) Titik Leleh (24) Titik Didih (19) Masa Molar (29) Densitas (24) Sifat Fisika (28) Sejarah Pengeboran Minyak (39) Pengolahan Air (26) Kapasitas Kalor (13) Penurunan Titik Beku (14) Kelimpahan CaCl 2 (6) Pengering (22) Sterilisasi Hewan (16) Makanan (10) Sumber Ion Kalsium (11) Kontrol Debu Jalan (17) Proses Indutri (5) Grup Ruang (12) Konstanta Kisi (25) Grup Titik (10) Geometri Koordinasi (15) Struktur Kristal (40) Entalpi Pembentukan Standar (20) Entropi Molar Standar (8; 9) Energi Bebas Gibbs (7) Termokimia (27) CaCl 2…”
Section: Struktur Dan Termokimiaunclassified
“…Sumber Viskositas (21) Medis (10 ) Kelarutan Dalam Air (18) Bau (23 ) Titik Leleh (24) Titik Didih (19) Masa Molar (29) Densitas (24) Sifat Fisika (28) Sejarah Pengeboran Minyak (39) Pengolahan Air (26) Kapasitas Kalor (13) Penurunan Titik Beku (14) Kelimpahan CaCl 2 (6) Pengering (22) Sterilisasi Hewan (16) Makanan (10) Sumber Ion Kalsium (11) Kontrol Debu Jalan (17) Proses Indutri (5) Grup Ruang (12) Konstanta Kisi (25) Grup Titik (10) Geometri Koordinasi (15) Struktur Kristal (40) Entalpi Pembentukan Standar (20) Entropi Molar Standar (8; 9) Energi Bebas Gibbs (7) Termokimia (27)…”
Section: Struktur Dan Termokimiaunclassified